Adherence to Antiepileptic Drugs and the Health Literacy of Caregivers in Childhood Epilepsy - Korkmaz, Muhammet Furkan; Erdem-Uzun, Mehmet; Korkmaz, Merve; Ekici, Arzu (Puerto Rico Health Sciences Journal, 2020)
Objective: To investigate the relationship between caregivers’ health literacy and adherence to treatment in children with epilepsy. Methods: The participants included 226 children and adolescents with epilepsy and their primary caregivers. The demographic and clinical characteristics were abstracted. An antiepileptic drug adherence assessment was done with the validated Morisky Medication Adherence Scale-8 (MMAS-8). According to the scale’s scoring system, 0 points indicates high adherence, 1 to 2 points, moderate adherence, and 3 to 8 points, low adherence. A 17-item public health literacy knowledge scale (PHLKS) was used to measure the caregivers’ levels of health knowledge. For this scale, higher scores indicate higher levels of health knowledge. A logistic regression model was used to evaluate the effects of demographic characteristics and clinical findings on full drug adherence. Results: The overall prevalence of complete drug adherence among patients was 47.3%. The median value of the MMAS-8 score was 1 point (0–8 points). The main reasons for high scores were forgetting to take medication (33.6%) and the difficulties in adhering to treatment (24.3%). The median of the PHLKS score was 13 points (4–17 points). According to the logistic regression results, patients in the 0 to 5 years age group were more likely to have full drug adherence than were those in the 12 to 18 years age group (OR [95% CI]: 2.9 [1.4–6.5]; p = 0.007). As the PHLKS score increased, drug adherence also significantly increased (OR [95% CI]: 0.8 [0.7–0.9]; p = 0.008). Conclusion: Age and caregivers’ health literacy knowledge were found to be significantly associated with adherence. To better define the factors associated with drug adherence in children with epilepsy, additional research (using objective, validated tools) aimed at determining caregivers’ health literacy is needed.